Axial compressive behavior of square steel tube confined rubberized concrete stub columns. (15th July 2022) - Zhaoyuan, Yang; Qiyun, Qiao; Wanlin, Cao; Xiaopeng, Gao
Abstract: An innovative square steel tube confined rubberized concrete column is proposed in this study to alleviate the pollution from waste rubber and improve the mechanical properties of conventional concrete. The axial compressive behavior of square steel tube confined rubberized concrete (Ru-STCC) stub column is experimentally studied. A total of thirty-two specimens, including four square steel tube confined concrete (STCC) stub columns and twenty-eight Ru-STCC stub columns, were fabricated and tested. The variables included rubber particle volume replacement ratio, steel tube thickness, rubber particle size and concrete strength grade. The failure mode, axial ultimate compressive strength, rigidity, ductility, strain characteristics, and confinement effects were analyzed. The results show that the failure modes of Ru-STCC specimens were the core concrete shear failure and steel tube buckling. Ultimate axial compressive strength and rigidity were found inversely proportional to the volume replacement ratio, When the volume replacement ratio reached 20%, the ultimate axial compressive strength and rigidity reduced by more than 20%. With the increase of steel tube thickness, the ultimate axial compressive strength increased by more than 10%. Concrete strength grade and rubber particle size have significant effects on rigidity and ductility, respectively. In addition, the differences between square concrete-filled in steel tube (CFST), rubberized concrete-filled in steel tube (Ru-CFST), STCC, and Ru-STCC stub columns were discussed by compressive strength and deformation capacity. The axial ultimate compressive strength of square Ru-STCC specimens was evaluated using various calculation models. The simplified formulae for the prediction of axial ultimate compressive strength were also presented. Highlights: An innovative square steel tube confined rubberized concrete column is proposed in this study. The failure mode, ultimate strength, rigidity, ductility and strain of square Ru-STCC specimens were analyzed. The differences between square CFST, Ru-CFST, STCC, and Ru-STCC stub columns were discussed. The axial ultimate strength of square Ru-STCC specimens was evaluated.